Primary Cilia as a Biomarker in Mesenchymal Stem Cells Senescence: Influencing Osteoblastic Differentiation Potency Associated with Hedgehog Signaling Regulation - Su Fu; Chunlin Zhang; Xu Yan; Dongzhe Li; Yongkui Wang; Chao Dong; Zhengming Cao; Yongming Ning; Chenglong Shao; Tengyue Yang (Hindawi Limited, 2021)
Bone tissue engineering-based therapy for bone lesions requires the expansion of seeding cells, such as autologous mesenchymal stem cells (MSCs). A major obstacle to this process is the loss of the phenotype and differentiation capacity of MSCs subjected to passage. Recent studies have suggested that primary cilia, primordial organelles that transduce multiple signals, particularly hedgehog signals, play a role in senescence. Therefore, we explored the relationships among senescence, primary cilia, and hedgehog signaling in MSCs. Ageing of MSCs by expansion in vitro was accompanied by increased cell doubling time. The osteogenic capacity of aged MSCs at passage 4 was compromised compared to that of primary cells. P4 MSCs exhibited reductions in the frequency and length of primary cilia associated with decreased intensity of Arl13b staining on cilia. Senescence also resulted in downregulation of the expression of hedgehog components and CDKN2A. Suppression of ciliogenesis reduced the gene expression of both Gli1, a key molecule in the hedgehog signaling pathway and ALP, a marker of osteoblastic differentiation. This study demonstrated that the senescence of MSCs induced the loss of osteoblastic differentiation potency and inactivated hedgehog signaling associated with attenuated ciliogenesis, indicating that primary cilia play a mediating role in and are biomarkers of MSC senescence; thus, future antisenescence strategies involving manipulation of primary cilia could be developed.